2022
DOI: 10.1039/d1cp05784g
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of electron transport in halogen incorporated diindenotetracene compounds: crystal structure, charge transport and optoelectronic properties

Abstract: Anisotropic electron mobility of halogenated diindenotetracene derivatives showing n-type characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…41 All possible crystal structures are selected by energy minimization of crystals with the most common space groups such as P2 1 ∕C, P1, P1, Pbca, P2 1 2 1 2 1 , P2 1 , C2∕c, Pna2 1 , Cc, Pbcn, and C2. 4,42,43,44,45 Crystal structure prediction method within the Polymorph Predictor module relies on Monte Carlo simulation which is a stochastic process. To assess the completeness of the search within this module, we have repeated the simulations for several times for each initial molecular structure until the same low energy crystal structures are produced.…”
Section: Computational Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…41 All possible crystal structures are selected by energy minimization of crystals with the most common space groups such as P2 1 ∕C, P1, P1, Pbca, P2 1 2 1 2 1 , P2 1 , C2∕c, Pna2 1 , Cc, Pbcn, and C2. 4,42,43,44,45 Crystal structure prediction method within the Polymorph Predictor module relies on Monte Carlo simulation which is a stochastic process. To assess the completeness of the search within this module, we have repeated the simulations for several times for each initial molecular structure until the same low energy crystal structures are produced.…”
Section: Computational Methodologymentioning
confidence: 99%
“…We generated large number of possible polymorphs using Dreiding force field parametrization which is considered to be a reasonable choice for organic molecules. 4,43,44,45 The charge transfer integrals of the designed NFAs are evaluated using the site energy correction method at the PW91/TZP level of theory using the ADF program. 46,47 The PW91/TZP theoretical level has been widely used to evaluate charge transfer integrals of organic molecules.…”
Section: Computational Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the introduction of halogen atoms into the organic scaffold may enhance the carrier mobilities of molecular and macromolecular materials. For example, fluorine atoms can enhance electron mobility due to their high electron affinity which results in a decrease in electron densities of the compounds. , Furthermore, the iodine atom enhances the hole mobilities of the developed materials as it reduces the local vibrating coupling, because of its heavy molecular weight. , Practically, though, iodine-functionalized materials cannot be exploited in optoelectronic applications due to their low stability . Although the electronegativities of bromine and iodine are comparable, bromine-functionalized materials often possess high stability which makes them suitable for optoelectronic devices .…”
Section: Introductionmentioning
confidence: 99%